The Concept of Social Entrepreneurship as a Form of Social Motives and Career Paths according to a Psychosocial Perspective - Yulianah (Neo Journal of economy and social humanities, 2023)
The notion of social entrepreneurship can offer answers to social problems prevalent in today's society, particularly in entrepreneurship and social innovation. The idea of social entrepreneurship is a brand-new and interesting research area that piques the interest of the vast majority of scholars currently working in the field. In the context of social entrepreneurship, this review aims to isolate pertinent research issues in social psychology. This investigation takes a qualitative approach and makes use of descriptive research tools. Due to the many investigative research, individual qualities, societal motivations, and a specific vocational identity were some of the possible psychosocial elements discovered necessary for this sort of entrepreneurship. In addition, various perspectives on society, organizational goals, and psychosocial aspects of organizational behaviour were incorporated.